2018
DOI: 10.1590/s1980-6574201800010001
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences in game-related statistics which discriminate winners from losers in elite basketball games

Abstract: -Aims:To advance knowledge of long-term development of basketball players, this study investigated age and sex differences in game-related statistics which discriminate winners from losers in World Basketball Championships held after the 2010 rule change. Methods: A total of 935 games from six categories (under-17, under-19 and open age for both men and women) were analyzed. All games were classified into three types (balanced, unbalanced and very unbalanced) according to point differential by a k-means clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
(19 reference statements)
1
14
0
1
Order By: Relevance
“…However, although international competitions are held not only for men, but also for women, previous studies on regional differences in basketball [2,3] have analyzed only men’s competitions. Sex differences in performance profiles have been reported in previous studies [4,5,6]. For example, Sampaio et al [4] analyzed the world championships for both men and women held in 2002 and reported that men’s teams were discriminated from women’s teams by a higher percentage of blocks and a lower percentage of steals, suggesting that anthropometric differences between men and women might be attributable to the difference in performance profiles.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, although international competitions are held not only for men, but also for women, previous studies on regional differences in basketball [2,3] have analyzed only men’s competitions. Sex differences in performance profiles have been reported in previous studies [4,5,6]. For example, Sampaio et al [4] analyzed the world championships for both men and women held in 2002 and reported that men’s teams were discriminated from women’s teams by a higher percentage of blocks and a lower percentage of steals, suggesting that anthropometric differences between men and women might be attributable to the difference in performance profiles.…”
Section: Introductionmentioning
confidence: 88%
“…Cohen’s d was calculated as an effect size and interpreted as follows: d = 0.20 to 0.49, small effect; d = 0.50 to 0.79, medium effect; d ≥ 0.80, large effect [25]. To identify game-related statistics that discriminate between the continents, a discriminant analysis was performed using R code ‘candis’ and ‘geneig’, which have been used in previous studies [3,6,11,26]. An absolute value of a structural coefficient (SC) greater than or equal to 0.30 was considered relevant for the discrimination between the continents [2,3].…”
Section: Methodsmentioning
confidence: 99%
“…Game-related statistics have been studied to scientifically illustrate the games in various categories: the Olympic Games for men 3,4,5 and women 6 , FIBA Basketball World Cup for men 7 , professional leagues for men 8,9,10 and women 11,12,13 , and international tournaments for youth athletes 14,15 . In addition, game-related statistics have been analyzed in various contexts such as effects of rule changes 16,17 , age and sex differences 18,19 , and relationship with physical fitness 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, international competitions are held not only for senior but also for junior (under-age categories) players. Since junior games have been reported to show different characteristics compared to senior games 18,19 , it is uncertain that the regional differences observed among the continental championships for seniors are also observed for juniors. If regional differences among continental championships for juniors are dissimilar to those for seniors, the previous findings on seniors 21 cannot be applied to juniors.…”
Section: Introductionmentioning
confidence: 99%
“…This is corroborated by the fact that a mere 15 months after the first experimental basketball match was played between two classes at Springfield YMCA (21 December 1891), Senda Berenson Abbott organized the first ever match between women's teams in this sport at Smith College, Northampton, Massachusetts, on 22 March 1893 (Simović and Pavlović, 2013). It must be said, though, that in the past decade the trend has been shifting and numerous papers have been published on this topic (Bazanov and Rannama, 2015;Conte and Lukonaitiene, 2018;Dimitros et al, 2013;Fylaktakidou et al, , 2013Koon et al, 2011;Kreivyte et al, 2013;Leicht et al 2017;Madarame 2018aMadarame , 2018bMadarame , 2018cMadarame , 2018dMilanović et al, 2016;Moreno et al 2013;Șentuna et al, 2018;Simović et al, 2017;Veleirinho and Tavares, 2013).…”
Section: Introductionmentioning
confidence: 99%